2007
DOI: 10.1002/da.20233
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the clinical characteristics of adolescent depressive disorders

Abstract: Our objective was to analyze differences in clinical characteristics and comorbidity between different types of adolescent depressive disorders. A sample of 218 consecutive adolescent (ages 13-19 years) psychiatric outpatients with depressive disorders was interviewed for DSM-IV Axis I and Axis II diagnoses. We obtained data by interviewing the adolescents themselves and collecting additional background information from the clinical records. Lifetime age of onset for depression, current episode duration, frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…This last fi nding is consistent with previous evidence that chronic depression aggregates in families [2••]. Similarly, Karlsson and colleagues [10] found that double depression was associated with an earlier age at onset, longer duration of index episode, and greater comorbidity (especially with anxiety disorders) than MDD.…”
Section: Distinction Between Chronic and Nonchronic Depressionssupporting
confidence: 91%
See 1 more Smart Citation
“…This last fi nding is consistent with previous evidence that chronic depression aggregates in families [2••]. Similarly, Karlsson and colleagues [10] found that double depression was associated with an earlier age at onset, longer duration of index episode, and greater comorbidity (especially with anxiety disorders) than MDD.…”
Section: Distinction Between Chronic and Nonchronic Depressionssupporting
confidence: 91%
“…Almost by defi nition, double depression and chronic MDD are more severe than dysthymic disorder with respect to symptomatology and functional impairment; however, few consistent differences between forms of chronic depression have been reported on other variables [2••, 10,13]. Moreover, longitudinal studies indicate that almost all patients with dysthymic disorder eventually experience exacerbations that meet criteria for MDEs [7•], suggesting that dysthymia and double depression are different phases of the same disorder.…”
Section: Distinction Between Dsm-iv Forms Of Chronic Depressionmentioning
confidence: 99%
“…Almost all of the interviewed subjects ( N = 218) had an ongoing episode of either unipolar or bipolar depression at baseline evaluation and were recruited to the study. Adolescent who declined to participate were similar to the study subjects in terms of age, sex, and parental socioeconomic status while they tended to have lower BDI-21 (19.0 versus 21.0, z = −1.93,    df = 371,    P = .05) and lower GHQ-36 (21.0 versus 24.0, z = −1.98,    df = 367,    P = .05) median sum scores [3, 8]. …”
Section: Methodsmentioning
confidence: 74%
“…The screening and diagnostic procedure and the study population ( n = 218) of the ADS study have been described in more detail previously [3, 28]. In brief, of the 774 consecutive outpatients, 660 (85.3%) were considered eligible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation